397 Direct Carotid Puncture for Mechanical Thrombectomy After Failed Peripheral Access: A Systematic Review and Meta-Analysis. (April 2023) - Domingo, Ricardo; Tripathi, Shashwat; Abello-Vaamode, Jorge; Singh, Rohin; Perez-Vega, Carlos; Ramos-Fresnedo, Andres; Tawk, Rabih G.
Abstract : INTRODUCTION: Direct carotid puncture (DCP) is an alternative route for mechanical thrombectomy (MT), especially in patients with difficult anatomy preventing access through the femoral or radial routes. However, DCP has increased morbidity and mortality due to access site complications related to cervical hematomas. METHODS: A systematic search of electronic databases from inception to March 2022 identified 197 related articles for screening. After applying inclusion and exclusion criteria, 10 studies were included, and data was extracted and analyzed using meta-analysis of proportions. RESULTS: 213 patients were included in this analysis, of which 44% also received intravenous thrombolysis. The overall success rate was 84% (95% CI, 73.66–90.85%; I 2 = 25.6%; p = 0.64). The average time to recanalization was 30.33 minutes (95%CI, 23.04–37.62 min; I 2 = 89.5%; p < 0.01) and 74% had good reperfusion (TICI >2a) (95% CI, 67–79%; I2 = 0%; p = 0.81). The overall complication rate was 20.38% (95%CI, 15.48–26.35%; I2 = 0%; p = 0.55). The rate of cervical hematomas was 18% (95% CI, 12–16%; I 2 = 70%; p = 0.27), of which 24.92% required surgical evacuation (95% CI, 27.5–95.9%; I 2 = 70%; p = 0.67). Other reported complications included carotid dissection, pseudoaneurysm, jugular vein puncture, and stroke related to access. The 90-day mortality rate from all causes was 35% based on 7 studies (95% CI, 22.5– 49.9%; I 2 = 44.8%; p = 0.08). The mRS at last follow-up was 4.09 (95% CI, 3.68–4.49; I 2 = 6.8%; p = 0.37). CONCLUSIONS: DCP is a reasonable alternative in patients that fail femoral and radial access for MT and the success rate of access with DCP is 84% with a TICI 2B or TICI 3 achieved in 74% of patients. The complications are mostly related to bleeding at the access site. The high rate of morbidity and mortality warrant further studies to improve the safety of DCP.